Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cells10071749
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization Strategies in Bone Tissue Engineering

Abstract: Bone is a highly vascularized tissue, and its development, maturation, remodeling, and regeneration are dependent on a tight regulation of blood vessel supply. This condition also has to be taken into consideration in the context of the development of artificial tissue substitutes. In classic tissue engineering, bone-forming cells such as primary osteoblasts or mesenchymal stem cells are introduced into suitable scaffolds and implanted in order to treat critical-size bone defects. However, such tissue substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 157 publications
(154 reference statements)
0
53
0
5
Order By: Relevance
“… Advantages and disadvantages of vascularization strategies. Created based on information from [ 7 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Advantages and disadvantages of vascularization strategies. Created based on information from [ 7 ]. …”
Section: Figurementioning
confidence: 99%
“…The differences between these two layers are rigidity and porosity. The cortical bone is less porous and presents better mechanical stiffness than cancellous bone, which has approximately ten percent of the cortical bone stiffness [ 7 , 8 , 9 ]. Osteons inside the cortical bone form units with a Haversian system containing nerves and blood vessels [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed key components of BTE [ 21 , 22 , 23 , 24 , 25 , 26 ]. According to these studies successful bone regeneration relies on the combination of (1) a bioactive scaffold [ 27 , 28 , 29 , 30 , 31 ]; (2) osteoprogenitor cells [ 21 , 26 , 32 , 33 , 34 , 35 ]; (3) growth factors (GF) [ 23 , 36 , 37 , 38 , 39 , 40 ] and (4) adequate vascularization [ 41 , 42 , 43 ] ( Figure 1 ).…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…Bone is a hierarchical structure with outer cortical bone and inner cancellous bone [ 1 , 2 , 3 ]. Its unique and complex structure determines its vital functions: protection, support, movement and hematopoiesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%